2020
DOI: 10.1186/s40814-020-00622-0
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for POSITIF, a randomised multicentre feasibility trial of a brief cognitive-behavioural intervention plus information versus information alone for the treatment of post-stroke fatigue

Abstract: Background: Approximately, half of stroke survivors experience fatigue. Fatigue may persist for many months and interferes with participation in everyday activities and has a negative impact on social and family relationships, return to work, and quality of life. Fatigue is among the top 10 priorities for 'Life after Stroke' research for stroke survivors, carers, and clinicians. We previously developed and tested in a small uncontrolled pilot study a manualised, clinical psychologist-delivered, face-to-face in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…9 Large interventional data are lacking to date, but recently the study protocol for an interventional study investigating cognitivebehavioral intervention including physical activity was published. 43 From our results, we cannot draw any conclusions about causality, but provide further observational support that physical activity merits evaluation as an intervention to treat PSF. Finally, we observed a correlation between insomnia and PSF that was significantly stronger in women as compared to men.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…9 Large interventional data are lacking to date, but recently the study protocol for an interventional study investigating cognitivebehavioral intervention including physical activity was published. 43 From our results, we cannot draw any conclusions about causality, but provide further observational support that physical activity merits evaluation as an intervention to treat PSF. Finally, we observed a correlation between insomnia and PSF that was significantly stronger in women as compared to men.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, a small randomized pilot trial demonstrated that the combination of cognitive–behavioral therapy and graded activity training was more effective than cognitive–behavioral therapy alone in treating PSF 9 . Large interventional data are lacking to date, but recently the study protocol for an interventional study investigating cognitive–behavioral intervention including physical activity was published 43 . From our results, we cannot draw any conclusions about causality, but provide further observational support that physical activity merits evaluation as an intervention to treat PSF.…”
Section: Discussionmentioning
confidence: 99%
“…CBT as a treatment for fatigue also seems promising in patients with neurological disease. It has shown to be effective in reducing severe fatigue in patients with multiple sclerosis [ 28 ] and is studied in treating post-stroke fatigue [ 29 , 30 ]. Whether fatigued patients with diffuse glioma could benefit from CBT to resolve or reduce fatigue remains to be determined.…”
Section: Introductionmentioning
confidence: 99%